Musical auditory processing, cognition, and psychopathology in 22q11.2 deletion syndrome. Issue 8 (16th November 2018) - Gao, Lucy; Tang, Sunny X.; Yi, James J.; McDonald‐McGinn, Donna M.; Zackai, Elaine H.; Emanuel, Beverly S.; Gur, Ruben C.; Calkins, Monica E.; Gur, Raquel E.
Abstract: Chromosome 22q11.2 deletion syndrome (22q11DS) is associated with impairment in multiple domains of cognition and risk for several psychiatric disorders. Musical auditory processing is highly heritable, and is impaired in individuals with schizophrenia and other neurodevelopmental disorders, but has never been studied in 22q11DS, notwithstanding anecdotal evidence of its sparing. We aimed to characterize musical auditory processing in 22q11DS and explore potential relationships with other cognitive domains, musical engagement, and psychiatric disorders. The Distorted Tunes Task and Global Musical Sophistication Index were used to assess pitch discrimination and general musical engagement in 58 individuals with 22q11DS aged 8–29 years. Psychopathology was assessed with sections from the modified Schedule for Affective Disorders and Schizophrenia for School‐Age Children and the Structured Interview for Prodromal Syndromes. The Penn computerized neurocognitive battery (CNB) examined four domains of cognition (executive functioning, episodic memory, complex cognition, and social cognition). Significant musical auditory processing impairment and reduced musical engagement were found in individuals with 22q11DS. However, deficits in musical auditory processing were not associated with reduced musical engagement. After covarying for age and sex, episodic memory and overall CNB performance accuracy were significantly related to performance in musical auditory processing. There were no relationships between musical auditory processing and presence of any psychiatric diagnoses. Individuals with 22q11DS experience significant deficits in musical auditory processing and reduced musical engagement. Pitch discrimination is associated with overall cognitive ability, but appears to be largely independent of psychiatric illness.